Clinical features and treatment outcomes in patients with T-cell large granular lymphocytic leukemia: A single-institution experience. (March 2020) - Zhu, Yangmin; Gao, Qingyan; Hu, Jing; Liu, Xu; Guan, Dongrui; Zhang, Fengkui
Highlights: CsA-based therapy is an effective option for the treatment of T-LGLL. HGB level predictive of initial response rate of T-LGLL. Modified regimens of high-dose CTX or ATG are safe and effective choices for patients with CsA refractory disease. New information regarding the clinical features and therapeutic strategies for T-LGLL. Abstract: Aim: Large granular lymphocyte leukemia (LGLL) is a rare lymphoproliferative disorder associated with failure of hematopoiesis and autoimmune diseases. This study describes the clinical features and treatment responses of 108 patients with T-cell large granular lymphocyte leukemia (T-LGLL). Methods: Clinical data were collected from T-LGLL patients treated at an anemia treatment center within the hematology and blood diseases unit of a single hospital from January 2009 to April 2019. Results: The majority of patients (78 %) were symptomatic at the time of presentation. Splenomegaly was observed in 41 % of cases, while hepatomegaly and lymphadenopathy were rare (6 % and 7 %, respectively). Cyclosporine (CsA) monotherapy was used as first-line therapy for 16 patients, with an overall response rate (ORR) of 56 %. CsA in combination with steroids was administered in 83 patients, with an ORR of 48 %. Among patients experiencing relapse or resistance to first-line therapy, 10 received antithymocyte globulin (ATG) therapy, with an ORR of 50 %; an additional 9 patients received a modified regimen of high-dose cyclophosphamide (CTX) therapy, yielding an ORR of 78 %. Conclusions: This study provides new information regarding the clinical features and therapeutic strategies for T-LGLL, which can be used to improve clinical decision making for T-LGLL patients. The data presented here indicate the CsA is an effective option for the treatment of T-LGLL, while modified regimens of high-dose CTX or ATG are safe and effective choices for patients with CsA refractory disease.